(untitled) (INNOVATIVE ECONOMY, 2020)
Yurkevych H.Y. SPIRITUAL WORLD OF PERSONALITY-MANAGER Purpose. The aim of the article is consideration of the category of spirituality in the activities of successful leaders as well as in understanding the essence of spirituality, the role of qualitative characteristics of the spirituality of the leader-personality to deepen the democratization of modern Ukrainian society in the process of its reformation. Methodology of research. The research is based on a systematic approach, the dialectical method of scientific knowledge, and the fundamental provisions of the theory of management psychology. General scientific and special methods of research are used for the scientific solution: the methods of scientific abstraction – for the substantiation of the categorical-conceptual apparatus; abstract and logical method – to formulate the conclusions of the study; methods of analysis, synthesis and synthesis – to study the main trends of management activity and its psychological background. Findings. It is proved that the managerial activity of the head according to his intellectual, communicative and professional potential, natural instincts and talent, abilities and skills can be effective in a concrete moral and psychological, ethno-psychological, social and cultural and environment. The interaction of management and society is explored. It was found out that the moral, legal, cultural requirements of a society in which management activities are carried out and actors and objects of management are found in traditions, rules of conduct, cultural values that determine the development of the direction of the personality of the leader (collective management subjects), the character of his character, the content of knowledge, his habits and abilities. Originality. It is established that professionalism is connected with the ability of a person to be successful in the chosen business, self-realization of her creative possibilities, quality of life in general. It is substantiated that highly professional personality of a professional is able to carry out acts in conscience, responsibly. Without studying the development and formation of the spiritual formation of the manager it is impossible to develop methodological and theoretical positions regarding its training as a specialist able to perform productively his management practice in a dynamically changing social and cultural situation. Practical value. The obtained results of the research will contribute to a significant improvement in management activities while conducting business and enrich the existing base of modern management psychology. Key words: professional, professionalism of activity, professionalism of the person, professional qualities of the leader, model of spiritual formation of the head, psychological training, thematic plan, spirituality, memory.